Interpenetration of Technological and Human Capital Assets in the Context of a Modernization Paradigm - Rogova O. V. Olga Vasilievna; Filippova T. V. Tatiana Vasilievna; Snopok I. R. Irina Ruslanovna; Kalashnikova T. V. Tatiana Vladimirovna (2016, 2016)
Title screen